PENERAPAN JURNALISTIK PROFETIK NILAI KEMANUSIAAN DALAM PEMBERITAAN DI RADAR LAMPUNG ONLINE - Beta Aprisindi; Fitri Yanti; Bambang Budiwiranto (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
This study examines the application of the humanitarian values ??of prophetic journalism in disaster reporting on the online media Radar Lampung Online. Using the Critical Discourse Analysis (AWK) approach modeled by Teun A. Van Dijk, this study analyzed six news texts published in November-December 2025. Aspects studied include macrostructure (topic/theme/title), superstructure (news scheme), microstructure (semantics, syntax, stylistics, rhetoric), and ideological representation through journalists language choices. The results show that humanitarian values ??(humanization) are present in all six news stories with varying degrees and forms. Journalists tend to use single sources from the government or authorities, position victims as passive objects, and construct disaster narratives from the perspective of the managers, not the managed. These findings indicate that the humanitarian values ??of prophetic journalism on Radar Lampung Online have been partially implemented: humanization is clearly manifested in the construction of the news, transcendence is present but not yet fully consistent, while liberation still needs to be strengthened so that the voices of affected communities can be better represented in the news narrative. This shows that Radar Lampung Online has attempted to apply humanitarian values ??in its reporting, but this application has not been carried out consistently and critically across all dimensions of prophetic journalism. Keywords: Prophetic Journalism, Human Values, Critical Discourse Analysis, Online Media